Numerical analysis of porous materials subjected to oblique crushing force. Issue 1 (January 2021) - Rogala, M; Gajewski, J
Abstract: This article presents an analysis of porous materials subjected to oblique loading. The analysis was carried out with the Abaqus software using the finite element method. The material model used for numerical analysis was Crushable Foam. The subject of the study involved solid elements located on a base with a variable angle of inclination. The values of the base angle were 15, 30, 45, 60 degrees. All samples were loaded with the same boundary conditions. During the test, the normal and shear forces were determined. The crushing efficiency indicators were calculated from the measured forces. The aim of the tests was to define the distribution of forces in the foam element.